2020
DOI: 10.21203/rs.3.rs-21628/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization and equilibrium studies for the removal of methylene blue from aqueous solution using activated bone char

Abstract: The surface characteristics as well as adsorption potential of activated cow bone char for the removal of methylene blue (MB) from aqueous solution were investigated. Physical characteristics of the adsorbent revealed a large surface area, low pore volume, reduced ash and moisture contents, which have been identified as good adsorption characteristics. The surface of the adsorbent was predominated by mesopores with a few microporous structures as well as the presence of carbonates, phosphates, silicates and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The results of the test analysis using XRD are shown in Figure4 (a). In this analysis, the hydroxyapatite content was confirmed by an X-ray diffractogram showing a strong peak at 33 0 In addition, the 2 Ɵ -axis peak between 25 0 and 60 0 also determined the presence of an apatite phase in the cow bone-activated charcoal material analyzed[26]. In general, the bone-activated charcoal diffraction pattern was close to the other bone-activated charcoal diffraction patterns obtained from pork and chicken bones[10,27].…”
supporting
confidence: 61%
“…The results of the test analysis using XRD are shown in Figure4 (a). In this analysis, the hydroxyapatite content was confirmed by an X-ray diffractogram showing a strong peak at 33 0 In addition, the 2 Ɵ -axis peak between 25 0 and 60 0 also determined the presence of an apatite phase in the cow bone-activated charcoal material analyzed[26]. In general, the bone-activated charcoal diffraction pattern was close to the other bone-activated charcoal diffraction patterns obtained from pork and chicken bones[10,27].…”
supporting
confidence: 61%
“…Previous studies had reported the effective use of cow bone for wastewater remediation . Cow bone had been adopted for the removal of methylene blue from aqueous solution [17]. Adsorption of hexavalent chromium from aqueous solution using cow bone had also been reported [18].…”
mentioning
confidence: 99%